Ca2+‐activated K+ channel (KCa) stimulation improves relaxant capacity of PDE5 inhibitors in human penile arteries and recovers the reduced efficacy of PDE5 inhibition in diabetic erectile dysfunction. (25th April 2013) - González‐Corrochano, R; La Fuente, JM; Cuevas, P; Fernández, A; Chen, MX; Sáenz de Tejada, I; Angulo, J
<x xml:space="preserve">Abstract</x> Background and Purpose We have evaluated the influence of calcium‐activated potassium channels (KCa) activation on cGMP‐mediated relaxation in human penile tissues from non‐diabetic and diabetic patients, and on the effects of PDE5 inhibitors on erectile responses in control and diabetic rats. Experimental Approach Cavernosal tissues were collected from organ donors and from patients with erectile dysfunction (ED). Relaxations of corpus cavernosum strips (HCC) and penile resistance arteries (HPRA) obtained from these specimens were evaluated. Intracavernosal pressure (ICP) increases to cavernosal nerve electrical stimulation were determined in anaesthetized diabetic and non‐diabetic rats. Key Results Concentration‐dependent vasodilation to the PDE5 inhibitor, sildenafil, in HPRA was sensitive to endothelium removal, NO/cGMP pathway inhibition and KCa blockade. Accordingly, activation of KCa with NS‐8 (10 μM) significantly potentiated sildenafil‐induced relaxations in HPRA (EC50 0.49 ± 0.22 vs. 5.21 ± 0.63 μM). In HCC, sildenafil‐induced relaxation was unaffected by KCa blockade or activation. Potentiating effects in HPRA were reproduced with an alternative PDE5 inhibitor (tadalafil) and KCa activator (NS1619) and prevented by removing the endothelium. Large‐conductance KCa (BK) and intermediate‐conductance KCa (IK) contribute to NS‐8‐induced effects and were immunodetected in human and rat penile arteries. NS‐8 potentiated sildenafil‐induced enhancement of erectile responses in rats. Activation of KCa recovered the impaired relaxation to sildenafil in diabetic HPRA while sildenafil completely reversed diabetes‐induced ED in rats only when combined with KCa activation. Conclusions and Implications Activation of KCa improves vasodilatory capacity of PDE5 inhibitors in diabetic and non‐diabetic HPRA, resulting in the recovery of erectile function in diabetic rats. These results suggest a therapeutic potential for KCa activation in diabetic ED.